2013
DOI: 10.1111/idj.12029
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in oral manifestations among HIV-infected Brazilian adults

Abstract: These data shows that oral manifestations are less prevalent in females than in males, particularly oral hairy leukoplakia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…In contrast, in the individuals in this study, no opportunistic oral lesions are detected, although some of them had medical history of oral candidiasis and Kaposi sarcoma before treatment. This finding is in agreement with other studies that evaluated patients treated with HAART, which found a relatively low prevalence of opportunistic oral lesions 31 , 32 . In the study of Dongo et al, 31 it was found that only 5% of individuals, from a total of 987 HIV+ individuals, had some opportunistic oral lesion.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, in the individuals in this study, no opportunistic oral lesions are detected, although some of them had medical history of oral candidiasis and Kaposi sarcoma before treatment. This finding is in agreement with other studies that evaluated patients treated with HAART, which found a relatively low prevalence of opportunistic oral lesions 31 , 32 . In the study of Dongo et al, 31 it was found that only 5% of individuals, from a total of 987 HIV+ individuals, had some opportunistic oral lesion.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with other studies that evaluated patients treated with HAART, which found a relatively low prevalence of opportunistic oral lesions 31 , 32 . In the study of Dongo et al, 31 it was found that only 5% of individuals, from a total of 987 HIV+ individuals, had some opportunistic oral lesion. Furthermore, Ramos et al 32 evaluated 1,232 HIV+ patients and found only 1.2% of necrotizing periodontal disease cases.…”
Section: Discussionsupporting
confidence: 93%
“…Fifty of 1439 studies met the criteria and were fully assessed . Unlike previous decades, the majority of the studies of this era (N = 43) were undertaken in developing countries.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic characteristics reported in the literature suggest a higher prevalence of OHL among HIV positive males, particularly homosexuals 1,18,19,20,21 . Our study likewise showed the male gender as the most affected, though the incidence of OHL among women had increased in the latest years.…”
Section: Discussionmentioning
confidence: 97%